Non-Immune-Mediated, p27-Associated, Growth Inhibition of Glioblastoma by Class-II-Transactivator (CIITA) - A Katherine Tan; Aurelie Henry; Nicolas Goffart; Christophe Poulet; Jacqueline A. Sluijs; Elly M. Hol; Vincent Bours; Pierre A. Robe (Cells)
Background: Previous works have shown that the expression of Class-II-Transactivator (CIITA) in tumor cells reduces the growth of glioblastoma (GB) in animal models, but immune effects cannot solely explain this. Here, we searched for immune-independent effects of CIITA on the proliferation of GB. Methods: Murine GL261 and human U87, GM2 and GM3 malignant glioma cells were transfected with CIITA. NSG (immunodeficient) and nude (athymic) mice were injected in the striatum with GL261-wildtype (-WT) and -CIITA, and tumor growth was assessed by immunohistology and luminescence reporter genes. Clonogenic, sphere-formation, and 3D Matrigel-based in vitro growth assays were performed to compare the growth of WT versus CIITA-expressing murine and human cells. Bulk RNA sequencing and RT2 qRT-PCR profiler arrays were performed on these four cell lines to assess RNA expression changes following CIITA transfection. Western blot analysis on several proliferation-associated proteins was performed. Results: The intracerebral growth of murine GL261-CIITA cells was drastically reduced both in immunodeficient and athymic mice. Tumor growth was reduced in vitro in three of the four cell types. RNA sequencing and RT2 profiler array experiments revealed a modulation of gene expression in the PI3-Akt, MAPK- and cell-cycle regulation pathways following CIITA overexpression. Western blot analysis showed an upregulation of p27 in the growth-inhibited cells following this treatment. PDGFR-beta was downregulated in all cells. We did not find consistent regulation of other proteins involved in GB proliferation. Conclusions: Proliferation is drastically reduced by CIITA in GB, both in vivo and in vitro, notably in association with p27-mediated inhibition of cell-cycle pathways.